Traffic engineering design : principles and practice - Slinn, Mike (Elsevier Butterworth-Heinemann, 2005)
This book introduces traffic engineering, covering not only implementation but social, environmental and legislative issues. Written by practitioners, Traffic Engineering Design offers practical solutions to real-life problems as well as explaining theory. The book has been fully updated to take account of recent developments in traffic engineering such as the growth of telematics and advanced signal control systems. It also considers the impact of new traffic management initiatives like congestion charging on the trafffic engineer. Concise introduction to traffic engineering Practical guidance on design and implementation Includes analysis of congestion charging.